2018
DOI: 10.1063/1.5023940
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroxyapatite addition on the mechanical properties of polyvinyl alcohol/chitosan biomaterials for bone scaffolds application

Abstract: The total antioxidant capacity and fluorescence imaging of selected plant leaves commonly consumed in Brunei Darussalam AIP Conference Proceedings 1933, 020001 (2018) Abstract. The increasing number of bone fracture incident in Indonesia from year to year needs an urgent problem solving of the limited bone substitute which can meet the necessary criteria for that purpose. Motivated by this, therefore, the current study is focusing on the optimization of material properties used as bone scaffold. A biomaterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In order to overcome the disadvantage of poor adherence to PVA, hydrogels with both bioactive and biocompatible components were developed by adding HA particles as a second reinforcing phase. The idea is not new, with several studies being reported in the literature [40,44,46,47,52]. For example, Wu et al [52] have incorporated HA into PVA hydrogel and developed a bioactive composite suitable for orthopedic applications such as artificial cartilage, studying the correlation between the immersion time in SBF (simulated body fluid) and the mechanical properties of these composites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the disadvantage of poor adherence to PVA, hydrogels with both bioactive and biocompatible components were developed by adding HA particles as a second reinforcing phase. The idea is not new, with several studies being reported in the literature [40,44,46,47,52]. For example, Wu et al [52] have incorporated HA into PVA hydrogel and developed a bioactive composite suitable for orthopedic applications such as artificial cartilage, studying the correlation between the immersion time in SBF (simulated body fluid) and the mechanical properties of these composites.…”
Section: Discussionmentioning
confidence: 99%
“…The observed features indicate that the presence of HA in PVA composites strongly influences the sample morphology, producing a fibrous and porous structure, which may provide advantages in using this material as soft tissue replacement, with interconnected small pores for micro-vascularization. At the same time, the presence of HA inside the "honeycomb" may have an important role in the adhesion ability of the osteogenic and chondrogenic precursor cells, supporting their differentiation, as well as the proliferation [44,45].…”
Section: Morphological Characterization By Semmentioning
confidence: 99%
“…FTIR analysis revealed overlapping stretching vibrations corresponding to CO and NH functional groups, confirming the presence of chitosan within the nanofiber matrix. Meanwhile, the characteristic PO 4 3− stretching group at wave number 1020.84-1041.56 cm −1 confirmed the presence of Hap [47], while the PO 4 3− bending group was observed at 588.28 cm −1 and the CO 3…”
Section: Ftir Analysismentioning
confidence: 89%
“…It is energy-efficient and environmentally friendly, making it a particularly attractive option for achieving this goal [7]. Composite scaffolds have better performance than monomaterial scaffolds [8,9]. Commonly used bone scaffold fabrication methods include gas foaming [10], solvent-casting [11], thermal phase separation [12], rapid prototyping [13], freeze-drying [14], and electrospinning [15].…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the ability of the scaffolds to swell and allow their pores to expand which facilitates the attachment and penetration of the bone cells into the scaffolds to grow in a 3D direction. On the other hand, a scaffold that swells too much can damage the frame structure and hinder cell attachment and growth [35]. Thus, the scaffolds must maintain a certain hydration state and keep a moderate intensity force.…”
Section: Swelling Behaviormentioning
confidence: 99%